Response of Tomato (Solanum Lycopersicum L) Plant Production By Providing Solid (Oil Palm Empty Fruit Bunch) and Rice Husk Charcoal - Rahmaniah Rahmaniah (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
Provision of Solid Made from Oil Palm Empty Fruit Bunches and Rice Husk Charcoal on Production of Tomato Plants (Solanum Lycopersicum L) aims to determine the effect of various types of Solid (Oil Palm Empty Fruit Bunches) and Rice Husk Charcoal on Production of Tomato Plants (Solanum Lycopersicum L). This research was conducted in Sona Village with an altitude of 18 meters above sea level Labuhanbatu Regency from December 2019 to March 2020. The material used was tomato seeds, husk charcoal, solid water. The equipment used was a 35x40 polybag, cutter blade, analytical balance, ruler, scissors, mortar, measuring flask, bucket, calipers, neat rope, hoe. The research will be conducted with a factorial group design. The first factor is the provision of Solid namely S0: Without Solid (Control), S1: 0.50 kg / polybag, S2: 0.70 kg / polybag S3: 1kg / polybag. The second factor is the administration of rice husk charcoal P0: Without Husk Charcoal (Control), P1: 0.2 kg/polybag, P2: 0.4 kg/polybag. The number of treatment combinations is 12 combinations. The research results indicate that the provision of Solid and Rice Husk Charcoal Against Tomato Plant Production (Solanum Lycopersicum L) has no significant effect on Stem Diameter (cm), Total Number of Fruits per Plant (g), Total Weight of Fruits per Plant (g). However, the treatment interaction of 1 kg/polybag of Solid and 0.2 kg/polybag of Rice Husk Charcoal can increase Stem diameter (cm), Total Number of Fruits per Plant (g), Total Weight of Fruits per Plant (g).